The contribution of alternative communication PECS - (method for exchanging figures) in the functional communication of autistic children (Research, Society and Development, 2021)
The present work has as general objective to analyze the increase of the functional interactions of the child with the applicability of alternative communication - PECS (method with exchanges of figures) with autistic children for the stimulation of verbal and functional communication; and as specific objectives: list the effectiveness and challenges encountered with the practice of alternative communication - PECS with autistic children; analyze the number of functional requests for verbal / functional interactions; observe the results of the practice of alternative PECS communication with autistic children. To achieve these goals, he sought theoretical support from authors such as Vygotsky (2001) Walter and Nunes (2008) Corrêa Netto (2013), among others. The approach chosen to support the study and achieve the objectives, was the review of the bibliographic production of literature. The qualitative study was elaborated from data present in selected scientific articles and published in the database of sites such as: Bireme, Scielo and Google Scholar and in scientific journals, using articles from 2015 to 2020. The analyzed studies allowed us to systematize theoretical contributions and contextual about the dimension of alternative communication PECS, as a fundamental element in language development, subject interaction and human development. The results showed a greater communicative interaction of the student in the intervention phase, in addition to generalizing the use of PECS-Adapted in the regular classroom. It was concluded that communication is one of the fundamental factors for the school inclusion of a student with ASD to occur more effectively.